2007
DOI: 10.1136/adc.2006.114082
|View full text |Cite
|
Sign up to set email alerts
|

Pertussis requiring intensive care

Abstract: Apnoea and paroxysmal cough are key symptoms of pertussis in those with shorter cough duration. Death or disability are frequent. Clinical factors define children at increased risk of these poor outcomes. Early discharge from PICU is associated with an increased risk of readmission and poor outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0
6

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 28 publications
2
50
0
6
Order By: Relevance
“…Hyperleukocytosis was an independent predictor of death among 13 critically ill infants with pertussis in the UK (Pierce, Klein and Peters 2000). Other studies showed that high leukocytosis was similarly predictive of death among pertussis infants in Canada (Mikelova et al 2003), New Zealand (Surridge, Segedin and Grant 2007), Argentina (Gentile et al 2014), Tunisia (Borgi et al 2014) and the USA (Murray et al 2013). Winter et al analyzed this association more closely in a larger study of fatal pertussis cases in the USA, finding that leukocytosis above 70 400 was particularly predictive of death, especially if combined with low birth weight (Winter et al 2015).…”
Section: Clinical Findings and Relationship To Fatal Pertussismentioning
confidence: 94%
“…Hyperleukocytosis was an independent predictor of death among 13 critically ill infants with pertussis in the UK (Pierce, Klein and Peters 2000). Other studies showed that high leukocytosis was similarly predictive of death among pertussis infants in Canada (Mikelova et al 2003), New Zealand (Surridge, Segedin and Grant 2007), Argentina (Gentile et al 2014), Tunisia (Borgi et al 2014) and the USA (Murray et al 2013). Winter et al analyzed this association more closely in a larger study of fatal pertussis cases in the USA, finding that leukocytosis above 70 400 was particularly predictive of death, especially if combined with low birth weight (Winter et al 2015).…”
Section: Clinical Findings and Relationship To Fatal Pertussismentioning
confidence: 94%
“…Given their increased risk of pertussis disease complications, caution in discharge planning for premature infants remains necessary, particularly if chronic lung disease is present. 18,19 In our study sample, children hospitalized with pertussis had a median of 4 inpatient days during their initial admission. This admission duration is the same as that for infants hospitalized with pertussis in the United States (1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004) and also in New Zealand during the most recent pertussis epidemic (2004-2005).…”
Section: Discussionmentioning
confidence: 99%
“…These include younger age, premature gestation, less complete immunization, intensity of exposure, receipt of macrolide antibiotics, presence of pneumonia or leukocytosis, and B pertussis serotype. 8,[14][15][16][17][18] We measured all of these except intensity of exposure and B pertussis serotype, and no associations with the readmission risk were evident. Nineteen percent of the children in this case series had a history of either low birth weight or were born prematurely.…”
Section: Discussionmentioning
confidence: 99%
“…She required intubation and ventilation and stayed in PICU for 9 days. The study from New Zealand comparing 1992 with 2003 shows us that infants are now being treated in PICU more often (11). Out of 72 children treated in PICU with pertussis, 97% were younger than 12 months old and 81% were less than 3 months old.…”
Section: Discussionmentioning
confidence: 99%